Cellulose Production Using Kombucha Culture From Wastewater of Tofu Industry (The Analysis Study on Sucrose and Ammonium Sulphate Additions and Its Production Cost) - Nurika, Irnia; Hidayat, Nur; Anggraeni, Yaumadina (Jurnal Teknologi Pertanian, 2007)
The objective of this research was to assess  the  influence of  sucrose and ammonium sulphate additions to the waste water of tofu industry as a substrate for Kombucha culture on  the produced cellulose sheet (pellicle) and to analyze its production cost. The experiment  was run in triplicates employing the Completely randomized block design. Three respective levels of  sucrose (8%, 10% and 12%) and ammonium sulphate (0.3%, 0.4% and 0.5%) were added. The parameters observed were the yield, moisture and crude fiber contents, and the production coct was then determined based on the most promising process. It was shown that the sucrose and ammonium sulphate additions  significant affected the yield, moisture and crude fiber contents, as well as the thickness of the pellicle produced. The best treatment was obtained by the addition of 10% (b/v) sucrose and 0.4% (b/v), ammonium sulphate which  resulted in the yield of  6.89% with the following characteristics: the thickness of 2.70 mm, and the respective moisture and crude fiber contents of 82.21% and 4.62%.  The production cost to achieve the break even point was Rp. 244,174.63 a pack of 7 kg. To get a profit level of 10%, the selling price of the product should be Rp. 299,500.00/pack.Key word : cellulose sheet, Kombucha, waste water